Conservative Management of Abnormally Invasive Placenta Previa after Midtrimester Foetal Demise - A. MacGibbon; Y. M. Ius (Case Reports in Obstetrics and Gynecology)
We present the case of a midtrimester intrauterine foetal demise (IUFD) in the context of abnormally invasive placentation. This was a grade 4 placenta previa with placenta increta in a patient requesting fertility conservation and was managed conservatively without immediate surgical intervention. The patient spontaneously delivered the fetus after 33 days, followed by a large obstetric haemorrhage requiring immediate laparotomy and hysterotomy. Her uterus was preserved and she went on to recover without further significant complication. While conservative management of morbidly adherent placentas has been well documented, there are no published cases of this strategy in the context of IUFD and fertility preservation.